La réalité en direct, l’actualité en spectacle (vivant) - Zoé Ververopoulou (Communication)
This article explores the issue of neo-documentary theatre and analyses the approaches and issues of a mini corpus of highly fact-based French performances that incorporate authentic documents and discourse into their dramaturgy. Instead of keeping to a fictional approach and taking on the role of the media, this type of theatre takes on a journalistic role, with a view to redefining the stage’s relationships with the world and reconnect with the problems of the modern world. The author looks at the dynamics of journalism and the socio-political scope of the genre, its quest for authenticity and objectivity, as well as the efforts to estheticize reality, and the tensions that they create.